Atividade antifúngica e indução de fitoalexinas por extratos de glândulas de anfíbios - Fernandes, Livia Deice Raasch (2017)
The class Amphibia have skin secretions consist of a variety of substances with protective function against microorganisms and larger predators. These substances are basically summarized by metabolism of the animal itself and has attracted the attention of researchers by the potential still unknown Therefore, the aim of this study was to evaluate the effect of crude extracts metanólicos obtained from skin secretions of two genera of the family Bufonidae, PRG (species 1) and PRM (species 2) in the induction of phytoalexins in soybean cotyledons and hypocotyl of beans and sorghum mesocotyls, enzyme activity in soybean cotyledons and, the action on isolates of Fusarium solani, Fusarium udum, Macrophomina phaseolina, Colletotrichum truncatum, Aspergillus flavus, Rhizoctonia solani e Calonectria pseudometrosideri. We used concentrations of 0.1; 0.2; 0.3; 0.4 and 0.5 mg/mL of extracts of secretions of the species 1 (PRG) and species 2 (PRM). For the testing of phytoalexins, it was applied as a negative control (sterile water) and a positive control (Saccharomyces cerevisiae 20%) and, for antifungal activity as a negative control (sterile water) and a positive control (fungicides pyraclostrobina+metconazole and azoxystrobin + cyproconazole). The tests for the production of phytoalexins were performed in triplicate and the data were expressed as absorbance (Abs) per gram of fresh tissue (gtf). In the enzymatic activity were used cotyledons after testing of production of phytoalexins. In the trials of antifungal activity was evaluated in mycelial growth (MG), production of microescleródios, sporulation (PIS), conidial germination (SGA) and appressorium formation (PIA). Based on the results of the extracts in the synthesis of phytoalexins showed that the extract of the secretions of the species PRG provided suppressive effect on production of gliceolina in soybean cultivar TMG 132 RR and showed no action on the cultivars TMG 4182 conventional and Monsoy 8372 IPRO. For the extract of secretions of PRM, the soybean cultivars, TMG 132 RR and Monsoy 8372 IPRO, showed induction at concentrations of 0.1 and 0.2 mg/mL and 0.2 mg/mL, respectively. In hypocotyl of beans, the extract of secretions of the species PRG is not increased production of faseolina. For the species PRM, there was a synthesis of faseolina the concentration 0.3 mg/mL in two bioassays performed. The extracts showed no activity in fitoalexínica sorghum mesocotyls. In the trials of enzymatic activity, we observed the Inductions of secretions of PRG in the activity of enzymes peroxidases and polyphenoloxidases and content of total protein in soybean cultivar TMG 132 RR. The extract from the species of PRM there was action induces the activity of peroxidases and polyphenoloxidases in soybean cultivars Monsoy 8372 IPRO and TMG 132 RR, respectively. The activity of β-1.3-glucanases in soybean cultivars TMG 132 RR and Monsoy 8372 IPRO is reduced as the increase in the concentration of the extracts of secretions of the species PRG and PRM, respectively. As for the trials in plant pathogens, the extract of secretions of the species PRG showed a reduction in the MG and IVCM of F. udum, F. solani, A. flavus and M. phaseolina in certain concentrations. The concentrations 0.1 and 0.2 mg/mL of extract induced the MG and IVCM of C. pseudometrosideri. In the extract of secretions of PRM, the concentration 0.5 mg/mL, in C. truncatum presented minor IVCM. In relation to PIG and sporulation, the extract of secretions of PRG, inhibitions in A. flavus, at concentrations 0.1 and 0.5 mg/mL. The production of microescleródios of R. solani was reduced at concentrations of 0.2 and 0.3 mg/mL of extract of secretions of the species PRM. In relation to the sink, the extract of skin secretions of PRG, there inhibitions from 85 to 99%, while in PRM, 63 to 100%. The results obtained in this study show promising effects with application of skin secretions of amphibian species, demonstrating phytoalexins activity and fungitoxic. Complementary studies that can distinguish the compounds that have these actions should be performed.